Te Wai Pounamu: The Greenstone Island: A History of Southern Maori during the European Colonization of New Zealand - Boast, Richard P (Victoria University of Wellington Law Review, 1994)
This article is a book review of HC Evison Te Wai Pounamu: The Greenstone Island: A History of Southern Māori during the European Colonization of New Zealand (Aoraki Press, Wellington and Christchurch, 1993). Evison was a Dunedin-based historian who has devoted much of his life to recording the history of the Ngāi Tahu people of the South Island. This book takes a broader approach, studying the southern Māori people on a scale that had been previously unseen. Boast argues that the book was the most comprehensive account available of the "deed" or "McLean era" transactions which typified land alienation in the period 1840-65 (between the Treaty of Waitangi and the establishment of the Native Land Court). Boast also argues that the book would have been more interesting had Evison used the Ngāi Tahu material to illuminate some of the contemporary debates among scholars as to why Māori sold so much land in the Native Land Court era. However, Boast concludes that Evison’s book is an excellent and comprehensive resource specialising in southern Māori.